Maternal autistic traits and anxiety in children with typical development in Chinese families: a moderated mediation model of mothers’ negative emotional expressions and child gender - Gu, Jiyou; Li, Tiantian; Dong, Huiqin (Frontiers in Psychology, 2024)
Background Prior studies have focused on the effects of maternal autistic traits on children with autism, but little attention has been paid to the effects of maternal autistic traits on typically developing children, while the mechanisms of the effects are not clear. Objective Given that, a moderated mediation model was conducted to examine the association between maternal autistic traits and typically developing children’s anxiety and the underlying mechanisms. Methods and results Participants were 648 mother–child dyads in which these children had no autistic siblings. Mothers reported their autistic traits and negative emotional expressions in the family and children’s anxiety. The results indicated that children’s anxiety was predicted by maternal autistic traits. Mediating analysis revealed that mothers’ negative emotional expressions partially mediated the association between their autistic traits and children’s anxiety. The findings also indicated that child gender moderated the relationship between maternal emotional expressions and children’s anxiety. Specifically, anxiety in girls was more strongly predicted by negative emotional expressions from their mothers than in boys. Conclusion These results have important theoretical and practical implications for reducing the adverse effect of maternal autistic traits on children’s anxiety, especially for girls. The present study also reveals that maternal negative emotional expression is an important mechanism. Causal conclusions cannot be drawn based on cross-sectional research design, so it is necessary to conduct longitudinal studies in the future.